BAURAN PEMASARAN DAN STRATEGI PENGEMBANGAN AGROINDUSTRI TAHU DI KOTA BANDAR LAMPUNG - Mutiara Rahmah; Ali Ibrahim Hasyim; Ktut Murniati (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
This research aims to analyze marketing mix, the internal and external environment, and development strategy of tofu agroindustry in Bandar Lampung City. This research uses a survey method. Respondents were owner, employee, consumers, and government which is taken purposively.  Technique sampling for consumers were purposive. The method of data analysis is descriptive analysis of 4P (product, price, place, and promotion) and SWOT analysis. The results show that different agroindustry scales, houshold level, medium, and large, applied marketing mix differently, the mix of the product, price, place, and promotion. Futher more, the intenal environment of the  agroindustry consists of product, management and funding, human resources, business location, and  marketing, while the external environment consists of economic, social and culture, competitors, technology, government policy, and consumers. Development strategies of tofu agroindustry household scale, medium, and large scale are the development of tofu production because of large demand, empowerment of the labor through training on modern technology, and marketing maintenance which are already extensive.Key words: development strategy, marketing mix, tofu